Using Instagram as a Marketing Strategy for American Restaurants in Surabaya during the Covid-19 Pandemic: Penggunaan Instagram Sebagai Strategi Pemasaran Restoran Amerika di Surabaya pada Masa Pandemi Covid-19 - Ahmadi, Daffa; Harianto, Didik (Universitas Muhammadiyah Sidoarjo, 2023)
The Covid-19 pandemic has an impact on various aspects. One of them is in the business aspect where the number of customers and sales turnover decreases, even businesses that are threatened with bankruptcy. however, jacks diner surabaya restaurant actually took this as their opportunity to establish a new Restaurant in Surabaya City. this becomes interesting to study because jacks diner surabaya restaurant established a restaurant during the covid-19 pandemic by using social media instagram and tiktok as their marketing strategy media. with the aim of attracting the attention of potential consumers. The strategy also aims to achieve high sales turnover. The purpose of this study was to identify and describe the marketing strategy of Jacks Diner Surabaya Restaurant with Instagram and TikTok which was carried out during the Covid-19 Pandemic. The research method used in this research is field qualitative with three-stage data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results of this study regarding the use of instagram and tiktok as marketing strategy media for the Jacks Diner Surabaya Restaurant, the manager argues that using Instagram social media which is used as a marketing strategy media is an effective and efficient media for their marketing strategy. This has a positive impact on the sales turnover aspect of Jacks Diner Surabaya Restaurant which shows an increase from April to July after innovating by using social media Instagram.